Rivals or Collaborators? Relational Ambidexterity and Absorption Speed. (September 2022) - Yu, Chengke; Yang, Haibin; Sun, He; (John) Lin, Zhiang
This study investigates how the configuration of rivals and collaborators within a firm's alliance portfolio affects its speed of absorbing external knowledge (i.e., absorption speed). While prior research on learning alliances has predominantly focused on interfirm overall knowledge flows, we contend that absorption speed plays a critical role in technology-intensive industries where time-based competition is paramount. Additionally, most previous studies do not clearly distinguish a firm's rivals from its collaborators within the alliance portfolio. Building on interorganizational learning theory, we propose that a simultaneous and balanced presence of both rivals and collaborators within a firm's alliance portfolio, which we term relational ambidexterity, increases the firm's speed of absorbing external knowledge. We further contend that while a firm's internal knowledge variety strengthens the positive relationship between relational ambidexterity and absorption speed, the number of common third parties between a firm and its partner weakens this positive relationship. The results of an event history study of 467 firms in the pharmaceutical industry of the United States from 1990 to 2010 provide general support for our hypotheses.